2023
DOI: 10.1302/2046-3758.121.bjr-2022-0263.r1
|View full text |Cite
|
Sign up to set email alerts
|

Femoral impingement in maximal hip flexion is anterior-inferior distal to the cam deformity in femoroacetabular impingement patients with femoral retroversion

Abstract: Aims Femoroacetabular impingement (FAI) patients report exacerbation of hip pain in deep flexion. However, the exact impingement location in deep flexion is unknown. The aim was to investigate impingement-free maximal flexion, impingement location, and if cam deformity causes hip impingement in flexion in FAI patients. Methods A retrospective study involving 24 patients (37 hips) with FAI and femoral retroversion (femoral version (FV) < 5° per Murphy method) was performed. All patients were symptomatic (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This would increase the risk of anterior femoroacetabular impingement (FAI), given the established association between reduced femoral torsion and anterior FAI [28]. In their recent study, Boschung et al successfully identified the areas of conflict around the hip joint in deep hip flexion for patients with reduced femoral torsion [1]. This conflict is prevented in individuals with increased femoral anteversion when MPTA is decreased.…”
Section: Discussionmentioning
confidence: 99%
“…This would increase the risk of anterior femoroacetabular impingement (FAI), given the established association between reduced femoral torsion and anterior FAI [28]. In their recent study, Boschung et al successfully identified the areas of conflict around the hip joint in deep hip flexion for patients with reduced femoral torsion [1]. This conflict is prevented in individuals with increased femoral anteversion when MPTA is decreased.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 30 , 35 Femoral retroversion alters the pattern of impingement, with the contact of the acetabular rim with the anteroinferior femoral neck, which should be considered during surgical planning. 29 , 36 Nonetheless, there is some concern that cam resection without capsular closure could increase joint microinstability due to the disruption of the labral seal in deep flexion. 37 …”
Section: Discussionmentioning
confidence: 99%
“…2,30,35 Femoral retroversion alters the pattern of impingement, with the contact of the acetabular rim with the anteroinferior femoral neck, which should be considered during surgical planning. 29,36 Nonetheless, there is some concern that cam resection without capsular closure could increase joint microinstability due to the disruption of the labral seal in deep flexion. 37 The FEA studies showed that cam FAI results in substantially elevated CP, 7,8,10,11 and in a DEA study the peak contact stress normalized after accurate arthroscopic cam correction.…”
Section: Labrum and Fai Pathomorphologymentioning
confidence: 99%